A novel method for optimizing epilepsy detection features through multi-domain feature fusion and selection - Kong, Guanqing; Ma, Shuang; Zhao, Wei; Wang, Haifeng; Fu, Qingxi; Wang, Jiuru (Frontiers in Computational Neuroscience, 2024)
The methods used to detect epileptic seizures using electroencephalogram (EEG) signals suffer from poor accuracy in feature selection and high redundancy. This problem is addressed through the use of a novel multi-domain feature fusion and selection method (PMPSO).Method: Discrete Wavelet Transforms (DWT) and Welch are used initially to extract features from different domains, including frequency domain, time-frequency domain, and nonlinear domain. The first step in the detection process is to extract important features from different domains, such as frequency domain, time-frequency domain, and nonlinear domain, using methods such as Discrete Wavelet Transform (DWT) and Welch. To extract features strongly correlated with epileptic classification detection, an improved particle swarm optimization (PSO) algorithm and Pearson correlation analysis are combined. Finally, Support Vector Machines (SVM), Artificial Neural Networks (ANN), Random Forest (RF) and XGBoost classifiers are used to construct epileptic seizure detection models based on the optimized detection features.Result: According to experimental results, the proposed method achieves 99.32% accuracy, 99.64% specificity, 99.29% sensitivity, and 99.32% score, respectively.The detection performance of the three classifiers is compared using ten-fold crossvalidation. Surpassing other methods in detection accuracy. Consequently, this optimized method for epilepsy seizure detection enhances the diagnostic accuracy of epilepsy seizures.